Eksplorasi Konsep Asuransi Syariah: Perspektif Hukum Islam dan Implementasinya - Diana Zalfanur; Erna Wijayanti; Ega Vivia Fatikhah; Marfita Hikmatul Aini; Muhammad Taufiq Abadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to understand the perspectives and concepts underlying sharia insurance, using a qualitative approach by utilizing in-depth analysis of secondary data from various related literature sources. The data collection technique used is a literature study technique to obtain a theoretical basis in the form of opinions or writings of legal experts, ulema and other authorized parties, regarding sharia insurance guidelines in Indonesia. This research is descriptive analytical in nature to analyze research results but is not used to make broader conclusions. The results of this research conclude that sharia insurance is an insurance product that is managed according to sharia and supervised by National Sharia Council - Indonesian Ulema Council. The function of sharia insurance is that it is managed according to sharia principles, transparent fund management, investment results are distributed to participants, ownership of funds by two parties, namely the company and participants, contribution funds are not forfeited even if there are no claims, and underwriting surplus benefits. The main aim of sharia insurance is to improve the welfare and struggles of the people. Sharia insurance business activities are regulated in Law no. 2 of 1992. One of the relevant company profiles is PT. JMA sharia insurance. Keywords: Sharia insurance, financial institutions, fund.